2003
DOI: 10.1152/japplphysiol.00508.2002
|View full text |Cite
|
Sign up to set email alerts
|

Relation of heart rate to percentV˙o 2 peak during submaximal exercise in the heat

Abstract: We tested the hypothesis that elevation in heart rate (HR) during submaximal exercise in the heat is related, in part, to increased percentage of maximal O(2) uptake (%Vo(2 max)) utilized due to reduced maximal O(2) uptake (Vo(2 max)) measured after exercise under the same thermal conditions. Peak O(2) uptake (Vo(2 peak)), O(2) uptake, and HR during submaximal exercise were measured in 22 male and female runners under four environmental conditions designed to manipulate HR during submaximal exercise and Vo(2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 25 publications
4
66
0
3
Order By: Relevance
“…The latter has been shown to produce an increase in heart rate of 7-8 beats·min Ϫ1 ·°C Ϫ1 (14,16,21). Hence, with progressive increases in ambient and concomitantly core temperature, the increase in heart rate during exercise-heat stress may be more pronounced for a given increase in %V O 2peak than in cooler conditions (2). Thus the proportional relationship between heart rate and relative exercise intensity that exists in COOL conditions (12) does not appear to extend to prolonged exercise performed in the heat, especially self-paced exercise.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The latter has been shown to produce an increase in heart rate of 7-8 beats·min Ϫ1 ·°C Ϫ1 (14,16,21). Hence, with progressive increases in ambient and concomitantly core temperature, the increase in heart rate during exercise-heat stress may be more pronounced for a given increase in %V O 2peak than in cooler conditions (2). Thus the proportional relationship between heart rate and relative exercise intensity that exists in COOL conditions (12) does not appear to extend to prolonged exercise performed in the heat, especially self-paced exercise.…”
Section: Discussionmentioning
confidence: 99%
“…3). Accordingly, it has been suggested that the increase in heart rate during sustained constant-load exercise in the heat is only partly related to the reduction in V O 2peak , with the remainder of the increase associated with other factors (2). The greater increase in heart rate is proposed to occur as a result of an elevation in sympathetic nervous activity and vagal withdrawal, as well as via the direct effect of blood temperature on the sinoatrial node (i.e., pacemaker tissue located in the right atrium) (16,21,22).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations